Correction: A new triazine based π-conjugated mesoporous 2D covalent organic framework: its in vitro anticancer activities. Issue 86 (16th October 2018) - Kanti Das, Sabuj; Mishra, Snehasis; Manna, Krishnendu; Kayal, Utpal; Mahapatra, Supratim; Das Saha, Krishna; Dalapati, Sasanka; Das, G. P.; Mostafa, Amany A.; Bhaumik, Asim
Abstract : Correction for 'A new triazine based π-conjugated mesoporous 2D covalent organic framework: its in vitro anticancer activities' by Sabuj Kanti Das et al., Chem. Commun., 2018, 54, 11475–11478.